(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
Nitro methane is an aprotic solvent with high polarity Which is used in a variety of applications(l) There is many . project between nitromethane and many kind of R - OH and Ar-OH at diffract temperature. But Less then between nitromethane and cyclic compound.